Gestión de Talento Humano en la Corporación “JAHER” S.A. Provincia de Los Ríos cantón Babahoyo - Chipre Chipre, Gladys Beatriz (2017)
Almacenes JAHER began its commercial activity in 1992, whose name derives from the first initials of the names of its owners Mr. Luis Jarrín Antón and Mrs. Sonia Cristina Herrera Flores, Jaher is launched to the market as a bazaar personally attended by its owners which since then are dedicated to the sale of furniture and appliances and different items for the home, spending the years as sole owner Mrs. Cristina Herrera managed to expand its company in different provinces of the country being its main headquarters Cuenca. JAHER benefits its clients with service at home, gifts for their purchases, one to four free quotas, among others